Genetic and clinical determinants of neonatal jaundice and growth patterns in the Qingdao birth cohort: A genome-wide association study - Xu Chen; Peina Du; Shuo Li; Xiaohong Wang; Mengyang Xu; Zhaobin Chu; Yue Zhang; Zhengyang Yao; Xuejie Huan; Yushan Huang; Mingyan Fang; Ya Gao; et al. (PLoS ONE, 2026)
Background Neonatal jaundice and early growth patterns are important indicators of early health, and genetic as well as clinical factors are known to influence these traits. However, evidence from East Asian newborns is still limited. Results This study presents a genome-wide association study (GWAS) investigating genetic determinants of Healthy Newborn Growth Indicators (HNGI), with a focus on neonatal jaundice (JAU), jaundice resolution (JAUR), birth weight (BW), and growth metrics (weight, height, BMI) measured within 90–105 days after birth. Our analysis identified 778 single-nucleotide polymorphisms (SNPs) across 120 genes significantly associated with HNGI. Among these associated variants, we found 12 missense mutations, seven of which are novel. The most significant association signal was for rs4148323 ( P = 2.3 × 10 −18 ) within the UGT1A gene locus, a well-established variant for JAU. Additionally, we discovered three novel missense mutations associated with JAU and JAUR. For BW, a novel missense mutation, rs148399850 ( P = 2.3 × 10 −8 ), was identified in the ATP7 gene, suggesting ATP7 as a potential functional regulator of birth weight. Analysis of allele frequency distributions across global and Chinese populations revealed distinct patterns of genetic diversity. Functional enrichment analysis of the candidate genes highlighted 18 genes significantly involved in 14 essential metabolic pathways related to growth and development. Furthermore, an analysis of clinical risk factors using data from the Biobank Japan (BBJ) demonstrated significant influences of various clinical conditions on HNGI. Conclusions This comprehensive analysis of newborns from the Qingdao cohort provides critical data for expanding molecular marker databases for prenatal screening, offering early warnings for jaundice, and guiding the healthy growth of newborns.